PEMBANGUNAN MODEL SISTEM SANITASI, PERPARITAN DAN PEMBENTUNGAN SEBAGAI ALAT BAHAN BANTU DALAM SUBJEK SISTEM SANITASI, PERPARITAN DAN PEMBENTUNGAN - Kong, H. P.; Yee, M. H.; Jailani, Md. Y.; Tee, T. K.; Kok, B. C.; Widad, O. (Online Journal for TVET Practitioners, 2018)
With the new technologies, one of the latest teaching approaches are teaching using model. The aim of this study is to develop a teaching model named Model Sanitation, Drainage and Sewerage System as a teaching aids among the teachers and students in construction technology course. The objective of this study is to develop a Model Sanitation, Drainage and Sewerage System by using a suitable materials, design and test the functionality as a teaching aids in subject Sanitation, drainage and sewerage system. The data is collected by using an instrument of study which is questionnaire form. Data analysis in this study is presented in percentage and frequency distribution. Researcher selected five respondents who specialize in the field of subject as the study sample. Through the analysis of data showed that the respondents are agreed that this Model Sanitation, Drainage and Sewerage System was suitable to be developed and can be used as an ABBM in subject Sanitation, Drainage and Sewerage System.